Potential Antifungal Targets against a Candida Biofilm Based on an Enzyme in the Arachidonic Acid Cascade—A Review - Liu, Xinning; Wang, Decai; Yu, Cuixiang; Li, Tao; Liu, Jianqiao; Sun, Shujuan (Frontiers in Microbiology, 2016)
Candida is an important opportunistic fungal pathogen, especially in biofilm associated infections. The formation of a Candida biofilm can decrease Candida sensitivity to antifungal drugs and cause drug resistance. Although many effective antifungal drugs are available, their applications are limited due to their high toxicity and cost. Seeking new antifungal agents that are effective against biofilm-associated infection is an urgent need. Many research efforts are underway, and some progress has been made in this field. It has been shown that the arachidonic acid cascade plays an important role in fungal morphogenesis and pathogenicity. Notably, prostaglandin E2 (PGE2) can promote the formation of a Candida biofilm. Recently, the inhibition of PGE2 has received much attention. Studies have shown that cyclooxygenase (COX) inhibitors, such as aspirin, ibuprofen and indomethacin, combined with fluconazole can significantly reduce Candida adhesion and biofilm development and increase fluconazole susceptibility; the MIC of fluconazole can be decrease from 64 to 2 μg/ml when used in combination with ibuprofen. In addition, in vivo studies have also confirmed the antifungal activities of these inhibitors. In this article, we mainly review the relationship between PGE2 and Candida biofilm, summarize the antifungal activities of COX inhibitors and analyze the possible antifungal activity of microsomal prostaglandin E synthase-1 (MPGES-1) inhibitors; additionally, other factors that influence PGE2 production are also discussed. Hopefully this review can disclose potential antifungal targets based on the arachidonic acid cascade and provide a prevailing strategy to alleviate C. albicans biofilm formation.